Multi-local analysis supports the transfer of Omolicna fulva to the genus Agoo and establishment of a new species in the genus from Costa Rica - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2025)
Recent survey work in Costa Rica has resulted in the discovery of a series of new species of derbid and cixiid planthoppers associated with palms. Here a new species of Agoo was collected by sweeping palms and is described as Agoo keili sp. nov. Sequence data are generated for the new species and Omolicna fulva for the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene and the D9 to D10 expansion region for the 28S rRNA gene to support the placement of the novel taxon in the genus Agoo. Omolicna fulva is transferred to Agoo, as A. fulvus comb. nov.